Effects of a natural preservative from sugarcane, and sodium lactate, on characteristics and acceptance of pressed ham - Brenes Rodríguez, Valeria (2022)
ABSTRACT.  Introduction: The reformulation of processed meat products is an important strategy in international plans to reduce sodium consumption. Objective: To compare the preserving action of sodium lactate with that of Proteria™ CV, based on sugarcane. Methods: We tested the preservtives during the refrigerated storage of pressed ham, in four combinations: sodium lactate, Proteria™ CV, a 50% - 50% mix of both, and no preservative as control. We evaluated total aerobic mesophilic microorganisms count, lactic acid bacteria count, pH, syneresis, texture, color and oxidative rancidity; as well as a discriminative sensory evaluation and a liking test with 100 consumers. Results: There were no differences in physical, chemical, and microbiological parameters. Consumers, however, reported a sensory difference. 67% of panelists liked all samples but prefered Proteria™ CV; 21% showed no preference but disliked the mixture; and 12% preferred the mixture. Conclusion: Proteria™ CV achieves a 30% reduction in sodium, and is accepted by consumers without generating significant quality changes.